Impact of Total Epinephrine Dose on Long Term Neurological Outcome for Cardiac Arrest Patients: A Cohort Study - Shi, Xiaowei; Yu, Jiong; Pan, Qiaoling; Lu, Yuanqiang; Li, Lanjuan; Cao, Hongcui (Frontiers in Pharmacology, 2021)
Introduction. Although epinephrine is universally acknowledged to increase return of spontaneous circulation (ROSC) after cardiac arrest, its balanced effects on later outcomes remain uncertain, causing potential harm during post-resuscitation phase. Recent studies have questioned the efficacy and potential deleterious effects of epinephrine on long-term survival and neurological outcomes, despite that the adverse relationship between epinephrine dose and outcome can be partially biased by longer CPR duration and underlying comorbidities. This study explored the long-term effect of epinephrine when used in a cohort of patients that underwent cardiac arrest during cardiopulmonary resuscitation. Methods. The data were originally collected from a retrospective institutional database from January 2007 to December 2015 and are now available on Dryad (via: https://doi.org/10.5061/dryad.qv6fp83). Use of epinephrine was coded by dose ( <2mg, 2 mg, 3 to 4 mg, ≥5 mg). A favorable neurological outcome was defined using a Cerebral Performance Category (CPC) 1 or 2. The association between epinephrine dosing and 3-month neurological outcome was analyzed by univariate analysis and multivariate logistic regression. Results. Univariate and multivariate analysis demonstrated a negative association between total epinephrine dose and neurological outcome. Of the 373 eligible patients, 92 received less than 2 mg of epinephrine, 60 received 2 mg, 97 received 3 to 4 mg and 124 received more than 5 mg. Compared to patients who received less than 2 mg of epinephrine, the adjusted odds ratio (OR) of a favorable neurological outcome was 0.8 (95% confidence interval [CI]: 0.38 to 1.68) for 2 mg of epinephrine, 0.43 (95% confidence interval [CI]: 0.21 to 0.89) for 3 to 4 mg of epinephrine and 0.40 (95% confidence interval [CI]: 0.17 to 0.96) for more than 5 mg of epinephrine. Conclusions. In this cohort of patients who achieved ROSC, total epinephrine dosing during resuscitation was associated with a worse neurological outcome three months after cardiac arrest, after adjusting other confounding factors. Further researches are needed to investigate the long-term effect of epinephrine on cardiac arrest patients.